International accounting and multinational enterprises - Radebaugh, Lee H (Wiley, 2006)
Includes access to practice set; Includes bibliographical references and indexes; International accounting and international business -- International accounting patterns, culture and development -- Comparative international financial accounting I -- Comparative international financial accounting II -- International financial statement analysis -- International transparency and disclosure -- International accounting standards and global convergence -- International business combinations, goodwill and intangibles -- International segment reporting -- Accounting for foreign currency -- International accounting for price changes -- Corporate governance and control of global operations -- Managing foreign exchange exposure -- International budgeting and performance evaluation -- International auditing issues -- International taxation issues